Validation of molecular markers for new stem rust resistance genes in U.S. hard winter wheat - Bernardo, Amy N.; Bowden, Robert L.; Rouse, Matthew N.; Newcomb, Maria S.; Marshall, David S.; Bai, Guihua (My University, 2013)
Stem rust, caused by Puccinia graminis f. sp. tritici (Pgt), is one of the most serious diseases of wheat (Triticum aestivum L.) worldwide. The discovery of new Pgt races in Africa, Ug99 and its variants, brings a new threat to global wheat production. Pyramiding several stem rust resistance genes into adapted varieties as opposed to breeding varieties with a single resistance gene is considered a more effective method to combat new races, but the success of gene pyramiding depends on the availability of molecular markers tightly linked to resistance genes. Markers for Ug99-effective genes, Sr2, Sr22, Sr26, Sr32, Sr35, Sr39, and Sr40, were evaluated for usefulness in marker-assisted selection (MAS) of hard winter wheat (HWW) using 10 resistance gene donor lines, 17 recently released U.S. HWW varieties or breeding lines, and 20 advanced introgression lines. Markers XcsIH81-BM and XcsIH81-AG for Sr22, Xsr26#43 and XBE51879 for Sr26, Xbarc55 for Sr32, Xbarc51 for Sr35, Xrwg27 for Sr39, Xsr39#22r for Sr40, and csSr2-derived single nucleotide polymorphism (SNP) marker for Sr2 are diagnostic for the set of HWW accessions evaluated in this study. These markers should be useful in marker-assisted pyramiding of stem rust resistance genes to develop HWW cultivars with multiple gene resistance against Ug99 races.
Citation: Bernardo, A. N., Bowden, R. L., Rouse, M. N., Newcomb, M. S., Marshall, D. S., & Bai, G. (2013). Validation of molecular markers for new stem rust resistance genes in U.S. hard winter wheat. Retrieved from http://krex.ksu.edu
Keywords: Stem rust; Puccinia graminis f. sp. tritici; Wheat; Gene pyramiding; Stem rust resistance